Pelatihan Entrepreuneurship Pada Pemuda Karang Taruna Batuang Sarumpun - Andre Ilyas; Nofritar Nofritar; Yuliarman Mahmudin (PT. TAKAZA INNOVATIX LABS, 2023)
Today's youth have received a qualified education. However, after graduating from school/college, youth still have the mindset of being a